An Instructional Model for Social Design Education: A Design Project for Stray Animals Including Production-Based Learning Approach - Yavuzcan, H. Güçlü; Şahin, Damla; Gür, Barış; Sevgül, Özden; Yavuz, Cemil (Design and Technology Education: An International Journal, 2019)
Social design education has become a significant part of industrial design education, thus new methodologies are required and being developed. One of these societal problems is animal welfare and human interaction with stray animals that is not a common topic amongst previous studies. This study presents a toolkit for social design teaching, combining social design thinking and product development processes to generate and realise design solutions for stray animals with a production-based learning approach. The toolkit consisting of nine phases under two processes was implemented into the secondyear ‘Product Design II’ 7-week studio project at Gazi University. A total of 35 sophomores taking the course offered during the second semester of the 2017/2018 academic year, participated in housing and feeding stations for a stray animals design project. To analyse the appropriateness of the toolkit, the submissions and process of the project were observed and evaluated by instructors and post-project questionnaires were employed to both instructors and students. The results revealed that this toolkit for social design education combining design thinking and product development processes improved industrial design students’ competencies and learning outcomes.